Simultaneous Formation of Ultrahigh Surface Area and Three-Dimensional Hierarchical Porous Graphene-Like Networks for Fast and Highly Stable Supercapacitors - Li, Yunyong; Li, Zesheng; Shen, Pei Kang (Advanced materials (Weinheim), 2013)
A new one‐step ion‐exchange/activation combination method using a metal‐ion exchanged resin as a carbon precursor is used to prepare a ultrahigh surface area and three‐dimensional hierarchical porous graphene‐like networks for fast and highly stable supercapacitors.